The Disenchantment of Urban Space. Some Remarks on the Arcades Project - Montanelli, Marina (Aisthesis, 2025)
In the Arcades Project many important pages are devoted by Walter Benjamin to the emergence of the labyrinthine exteriority of the modern metropolis, to its peculiar phantasmagorias and to the problem of the critical awakening or disenchantment of urban space itself. According to Benjamin’s method of dialectical thought by «polarity», the metropolis is presented, at the same time, as hell and as a space, material and cognitive, of revolution. This article aims to explore the dialectical image of this specific awakening: the barricade. What is more, the intention is to delve into the connections between such an idea of disenchantment and the problem of art (which begins in this century to become reproducible and to confront itself with the laws of the capitalist market), between this dialectical image and the principle of montage, between political revolution and revolution of sensibility.